1, 2, 3-Triazole-assisted C–H amidation by cobalt(iii) catalysis. Issue 11 (18th August 2017) - Yu, Xinling; Ma, Qiang; Lv, Songyang; Li, Jue; Zhang, Chen; Hai, Li; Wang, Qiantao; Wu, Yong
Abstract : This protocol proceeded efficiently under external oxidant-free conditions with the advantages of high atom efficiency and a broad substrate scope. Abstract : A procedure for the [Cp*Coiii ]-catalyzed, 1, 2, 3-triazole directed C–H amidation of arenes, using dioxazolone as an efficient amidating reagent, has been developed. This reaction provides a step- and atom-economical protocol for C–N bond formation, releasing carbon dioxide as a single byproduct. Yet a variety of functional groups are well tolerated, obtaining the desired products in moderate to excellent yields.